Analisis Pengaplikasian Syariah Compliant di Hotel Rangkayo Basa Padang Panjang - Ferawati Ferawati; Alimin Alimin (i-Tourism: Jurnal Pariwisata Syariah, 2021)
This study aims to determine whether the Rangkayo Basa Padang Panjang Hotel has implemented MUI Fatwa No. 108/DSN-MUI/X/2016 and also to find out whether it is appropriate for the Rangkayo Basa Hotel Padang Panjang to be said to be a sharia hotel. The research used is a type of qualitative research. The data collection technique that the author uses is interviews, observation and data processing is carried out in a qualitative descriptive manner, then described and classified into certain aspects of the problem and explained through effective sentences. The results showed that in the implementation and implementation of MUI Fatwa No. 108/DSN-MUI/X/2016 concerning Guidelines for the Implementation of Tourism Based on Sharia Principles at the Rangkayo Basa Hotel Padang Panjang it was found that the Rangkayo Basa Padang Panjang Hotel was in accordance with the DSN-MUI Fatwa, except for a few things, namely: a) Rangkayo Basa Padang Panjang Hotel have not received a halal certificate from MUI for food and drinks because it has not been issued by MUI until now, b) Rangkayo Basa Padang Panjang Hotel has not provided facilities for worship such as, hotel rooms do not have the sound of the call to prayer when prayer time has entered, c) Rangkayo Basa Hotel Padang Panjang has implemented the Ijarah contract, the Wakalah bil ujrah contract and has not implemented the Ju'alah contract due to the COVID-19 outbreak. While the obstacles in the implementation of the MUI Fatwa No. 108/DSN-MUI/X/2016 is the selection of hotel guests who want to stay for hotel guests who bring a partner at Hotel Rangkayo Basa Padang Panjang.